1997
DOI: 10.1046/j.1365-2141.1997.1933010.x
|View full text |Cite
|
Sign up to set email alerts
|

Clonal haemopoiesis in normal elderly women: implications for the myeloproliferative disorders and myelodysplastic syndromes

Abstract: Summary. Studies of X chromosome inactivation patterns are central to many aspects of our understanding of the pathogenesis of haematological malignancies. In patients with myeloproliferative disorders and myelodysplastic syndromes the demonstration of skewed X inactivation patterns in multiple haemopoietic lineages has been taken to indicate a stem cell origin for these groups of diseases. However, stem cell depletion or selection pressures can also produce skewed X inactivation patterns and might increase wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(108 citation statements)
references
References 39 publications
7
100
1
Order By: Relevance
“…26 Excessively skewed XCIPs are also found in hematopoietic cells of healthy elderly females (ϳ40% of individuals older than 60 years of age). [27][28][29] This acquired skewing is mainly because of selective pressure for one or more genetic differences between the two X-chromosomes. 30 -32 Apart from false clonality, false polyclonality may be observed.…”
Section: Discussionmentioning
confidence: 99%
“…26 Excessively skewed XCIPs are also found in hematopoietic cells of healthy elderly females (ϳ40% of individuals older than 60 years of age). [27][28][29] This acquired skewing is mainly because of selective pressure for one or more genetic differences between the two X-chromosomes. 30 -32 Apart from false clonality, false polyclonality may be observed.…”
Section: Discussionmentioning
confidence: 99%
“…These results have subsequently been confirmed by other investigators. [40][41][42] Since the incidence of skewing may vary more than fourfold depending on the age of the population, it is clear that the age of the cohort analyzed may constitute the major confounding factor explaining the discrepancy of previous studies.…”
Section: Study Of the Normal Female Population: Unequal Lyonization Rmentioning
confidence: 99%
“…Alternatively, polymorphisms in genes located on the X-chromosome may lead to selection of cells with one particular active X-chromosome and to a skewed XCIP. 7,8 Such polymorphisms should be present in genes regulating the decision of self-renewal or differentiation after stem cell division, or in genes affecting growth rate or survival of cells. Abkowitz et al 19 have shown in cats that acquired skewing of XCIP is likely to be caused by a polymorphic gene on the X-chromosome.…”
Section: Figurementioning
confidence: 99%
“…However, several reports have shown an increase in the number of females with a skewed XCIP in blood leukocytes with increasing age. [7][8][9][10][11] The percentage of females with a ratio of more than 75% of either allele in granulocytes may be as high as 40% after the age of 65. The skewing in T cells seems to lag behind, which may give rise to a different XCIP for T cells and granulocytes.…”
Section: Introductionmentioning
confidence: 99%